Severe haemophilia A patients have reduced numbers of peripheral memory B cells - Irigoyen, María Belén (2011)
The development of inhibitors is a complication of replacement treatment in Haemophilia. Loss of FVIII-specific memory B cells in the spleen is associated to down regulation of antibodies in mice treated with high doses of FVIII, but changes in B cell memory have not been described in haemophilic patients.  The aim of this study was to evaluate the phenotype of circulating lymphocytes in Severe Haemophilia A. Twenty patients with inhibitors (PI), 22 without inhibitors (P), 9 patients during Immune Tolerance Induction (ITI) treatment and 20 healthy donors (HD) were included. Peripheral blood lymphocytes were  examined by flow cytometry. Anti-FVIII antibodies were measured by Bethesda and flow cytometry. Percentages of T subsets and B lymphocytes were similar in all groups. But memory B cells (CD27+) were decreased in PI and P compared to HD but the level of significance was higher in PI (p=0.001) than P (p=0.01). PI with high level of anti-FVIII antibodies presented the lowest B memory values. CD70 expression was also lowest in PI. Non-switched CD27+ subpopulation (IgD+) was prevalent in PI but did not show statistical significance. When ITI failed, the percentages of CD27+ B cells after 12 months of ITI were lowest. In a longitudinal study performed in 4 patients, an increased percentage of CD27+ and CD70+ B cells during ITI was found. This work suggests that different peripheral lymphocyte markers as CD27 an CD70 on B cells, may be helpful to evaluate anti-FVIII response and to monitor the success of ITI.